Netrin‐1 overexpression improves neurobehavioral outcomes and reduces infarct size via inhibition of the notch1 pathway following experimental stroke. Issue 9 (13th January 2017) - Yang, Xiaosheng; Li, Shiting; Li, Bin; Wang, Xiaoqiang; Sun, Chongran; Qin, Haiqiang; Sun, Hui
Abstract: Stroke is a leading cause of morbidity and mortality worldwide. Administration of Netrin‐1 during the peri‐infarct period has been shown to decrease infarct size in rats; however, the underlying mechanism is unclear. We addressed this question in the present study by inducing stroke in rats via middle cerebral artery occlusion (MCAO), and evaluating the effects of Netrin‐1 treatment by neurobehavioral testing, immunocytochemistry, and western blotting. Netrin‐1 overexpression increased neurobehavioral test scores and reduced cerebral infarct volume following MCAO via inhibition of the Notch1 signaling pathway. These results demonstrate that early administration of Netrin‐1 can is an effective therapeutic approach for improving outcome after stroke. © 2017 Wiley Periodicals, Inc. Abstract : Netrin‐1 overexpression increased neurobehavioral test scores and reduced cerebral infarct volume following middle cerebral artery occlusion. Under these conditions, Notch1 and Jagged1 were colocalized at the cell surface but not within the cell, the complex was not internalized and the downstream effects of Notch1 signaling were abrogated.